Comparative Genomics of Chrysochromulina Ericina Virus and Other Microalga-Infecting Large DNA Viruses Highlights Their Intricate Evolutionary Relationship with the Established Mimiviridae Family - Gallot-Lavallée, Lucie (J Virol, 2017)
Chrysochromulina ericina virus CeV-01B (CeV) was isolated from Norwegian coastal waters in 1998. Its icosahedral particle is 160 nm in diameter and encloses a 474-kb double-stranded DNA (dsDNA) genome. This virus, although infecting a microalga (the haptophyceae Haptolina ericina, formerly Chrysochromulina ericina), is phylogenetically related to members of the Mimiviridae family, initially established with the acanthamoeba-infecting mimivirus and megavirus as prototypes. This family was later split into two genera (Mimivirus and Cafeteriavirus) following the characterization of a virus infecting the heterotrophic stramenopile Cafeteria roenbergensis (CroV). CeV, as well as two of its close relatives, which infect the unicellular photosynthetic eukaryotes Phaeocystis globosa (Phaeocystis globosa virus [PgV]) and Aureococcus anophagefferens (Aureococcus anophagefferens virus [AaV]), are currently unclassified by the International Committee on Viral Taxonomy (ICTV). The detailed comparative analysis of the CeV genome presented here confirms the phylogenetic affinity of this emerging group of microalga-infecting viruses with the Mimiviridae but argues in favor of their classification inside a distinct clade within the family. Although CeV, PgV, and AaV share more common features among them than with the larger Mimiviridae, they also exhibit a large complement of unique genes, attesting to their complex evolutionary history. We identified several gene fusion events and cases of convergent evolution involving independent lateral gene acquisitions. Finally, CeV possesses an unusual number of inteins, some of which are closely related despite being inserted in nonhomologous genes. This appears to contradict the paradigm of allele-specific inteins and suggests that the Mimiviridae are especially efficient in spreading inteins while enlarging their repertoire of homing genes. IMPORTANCE Although it infects the microalga Chrysochromulina ericina, CeV is more closely related to acanthamoeba-infecting viruses of the Mimiviridae family than to any member of the Phycodnaviridae, the ICTV-approved family historically including all alga-infecting large dsDNA viruses. CeV, as well as its relatives that infect the microalgae Phaeocystic globosa (PgV) and Aureococcus anophagefferens (AaV), remains officially unclassified and a source of confusion in the literature. Our comparative analysis of the CeV genome in the context of this emerging group of alga-infecting viruses suggests that they belong to a distinct clade within the established Mimiviridae family. The presence of a large number of unique genes as well as specific gene fusion events, evolutionary convergences, and inteins integrated at unusual locations document the complex evolutionary history of the CeV lineage.